2020
DOI: 10.3390/ijerph17041428
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Financial Development on Energy Consumption: Worldwide Evidence

Abstract: In this study, we investigated the influence of overall financial development and its components on energy consumption using the panel data of 120 countries and the generalized method of moments (GMM). By dividing the sample into developed and developing countries, we further examined the national differences of the impact of financial development on energy consumption. The empirical results indicate that the overall financial development significantly positively impacts energy consumption from a worldwide per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 52 publications
(76 reference statements)
7
40
1
Order By: Relevance
“…The AR (1) estimates were insignificant, whereas those for AR (2) were insignificant. The Sargan test results were insignificant, suggesting that the null hypothesis of jointly valid instrumental variables has not been ignored (Ma & Fu, 2020). The interaction method is applied to check the moderator effect of interest rate and firm size on the debt to capital ratio (Youn, Hua, & Lee, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The AR (1) estimates were insignificant, whereas those for AR (2) were insignificant. The Sargan test results were insignificant, suggesting that the null hypothesis of jointly valid instrumental variables has not been ignored (Ma & Fu, 2020). The interaction method is applied to check the moderator effect of interest rate and firm size on the debt to capital ratio (Youn, Hua, & Lee, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…e long run association among the variables has been found in his study for Pakistan. More recently, Ma and Fu [37] have studied the impact of financial development on energy consumption in 120 countries by using GMM model. ey found that overall system of financial development positively and significantly affects energy consumption in the sample.…”
Section: Energy Consumption and Carbon Emissionmentioning
confidence: 99%
“…Most of the scholars have discovered a positive influence of financial sector development on energy use for different countries and country groups [12][13][14][15]. Furthermore, energy use can affect the development of the financial sector, because the acquisition and use of houses, buses, cars, refrigerators, and dishwashers can influence the money needs of individuals [16].…”
Section: Introductionmentioning
confidence: 99%
“…Financial institution access can also positively affect energy use by facilitating access to finance for both people and companies that will support investments and will increase demand for energy-intensive commodities [14]. However, financial inclusion enables the economic units to make more energy-efficient investments and to buy more energy-efficient commodities, having a direct influence on global energy consumption.…”
Section: Introductionmentioning
confidence: 99%